Treatment with N-acetyl-seryl-aspartyl-lysyl-proline prevents experimental autoimmune myocarditis in rats - Nakagawa, Pablo (2012)
Myocarditis is commonly associated with cardiotropic infections and has been linked to development of autoimmunity. N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) is a naturally occurring tetrapeptide that prevents inflammation and fibrosis in hypertension and other cardiovascular diseases; however, its effect on autoimmune-mediated cardiac diseases remains unknown. We studied the effects of Ac-SDKP in experimental autoimmune myocarditis (EAM), a model of T cell-mediated autoimmune disease. This study was conducted to test the hypothesis that Ac-SDKP prevents autoimmune myocardial injury by modulating the immune responses. Lewis rats were immunized with porcine cardiac myosin and treated with Ac-SDKP or vehicle. In EAM, Ac-SDKP prevented both systolic and diastolic cardiac dysfunction, remodeling as shown by hypertrophy and fibrosis, and cell-mediated immune responses without affecting myosin-specific autoantibodies or antigen-specific T cell responses. In addition, Ac-SDKP reduced cardiac infiltration by macrophages, dendritic cells, and T cells, pro-inflammatory cytokines [interleukin (IL)-1α, tumor necrosis factor-α, IL-2, IL-17] and chemokines (cytokine-induced neutrophil chemoattractant-1, interferon-γ-induced protein 10), cell adhesion molecules (intercellular adhesion molecule-1, L-selectin), and matrix metalloproteinases (MMP). Ac-SDKP prevents autoimmune cardiac dysfunction and remodeling without reducing the production of autoantibodies or T cell responses to cardiac myosin. The protective effects of Ac-SDKP in autoimmune myocardial injury are most likely mediated by inhibition of 1) innate and adaptive immune cell infiltration and 2) expression of proinflammatory mediators such as cytokines, chemokines, adhesion molecules, and MMPs.